Denise Levertov : a poet's life - Greene, Dana (University of Illinois Press, 2012)
Kenneth Rexroth called Denise Levertov (1923-1997) "the most subtly skillful poet of her generation, the most profound ... and the most moving." Author of twenty-four volumes of poetry, four books of essays, and several translations, Levertov became a lauded and honored poet. Born in England, she published her first book of poems at age twenty-three, but it was not until she married and came to the United States in 1948 that she found her poetic voice, helped by the likes of William Carlos Williams, Robert Duncan, and Robert Creeley. Shortly before her death in 1997, the woman who claimed no country as home was nominated to be America's poet laureate. In this illuminating biography, Dana Greene examines Levertov's interviews, essays, and self-revelatory poetry to discern the conflict and torment she both endured and created in her attempts to deal with her own psyche, her relationships with family, friends, lovers, colleagues, and the times in which she lived. Denise Levertov: A Poet's Life is the first complete biography of Levertov, a woman who claimed she did not want a biography, insisting that it was her work that she hoped would endure. And yet she confessed that her poetry in its various forms--lyric, political, natural, and religious--derived from her life experience. Although a substantial body of criticism has established Levertov as a major poet of the later twentieth century, this volume represents the first attempt to set her poetry within the framework of her often tumultuous life.